POVERTY ALLEVIATION AND COMMUNITY WELFARE: A CASE STUDY IN BONDOWOSO REGENCY, EAST JAVA, INDONESIA - Wulandari, Kusuma; Rosfiantika, Evi (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
Poverty and social welfare are inseparable indicators of poverty alleviation. The purposes of this study were to describe the distribution of poverty in Bondowoso Regency, East Java Province using welfare indicators and to overview the efforts had been made by the local government in tackling the poverty problems. The research was carried out using a qualitative descriptive method by referring to the secondary data with interactive model analysis. Based on the welfare-related issues that consisted of house ownership status, level of welfare, school drop out ,access to electricity, quality of water source, access to subsidized LPG, sanitation facility, working family members, and access to health service, there were five sub-districts of the regency experiencing acute deprivation. At regency level, all these issues were shared in equal proportions in contributing the poverty incidence across the twenty-three sub-districts. There were twelve sub- districts faced poverty problems by complying with at least two welfare issues. The highest level of poverty was found at Wringin Sub-district with six welfare issues, followed by Taman Krocok and Botolinggo Sub-districts with five welfare issues, and Klabang and Cerme Sub-districts with four welfare issues. Although a number of programs related to poverty eradication have been delivered, the root causesof poverty and welfare would still remain unsolved. Special attention and serious handlings for welfare improvement should be given to those sub-districts. The integrated program activities involving various parties should be taken into account to improve the effectiveness of the program as to the poverty alleviation in the Regency.